Congenital tuberculosis causing hydrops fetalis: A case report and review of literature - Eshita Bansal; Shuchi Mehra; Kapil Bhalla (Journal of Family Medicine and Primary Care)
Tuberculosis (TB) is an infectious disease of which congenital TB is a rare form even in TB-endemic countries such as India. There are very few case reports of the same in the literature. Though the incidence rate of congenital TB is low, mortality rates are very high. Here, we report a case of a 2-day-old neonate who presented to Pediatrics Accident and Emergency with complaints of fast breathing and swelling all over the body. The baby had swelling all over the body and subcutaneous edema suggestive of hydrops fetalis. She was investigated and subsequently diagnosed to have congenital TB for which appropriate treatment was started. The baby is still on regular follow-up with no active complaints.